Deep brain stimulation of the pedunculopontine nucleus in Parkinson's disease. Preliminary experience at Oxford. - Pereira, E; Muthusamy, K; De Pennington, N; Joint, C; Aziz, T (2008)
Deep brain stimulation (DBS) of the pedunculopontine nucleus (PPN) is a novel neurosurgical therapy developed to address symptoms of gait freezing and postural instability in Parkinson's disease and related disorders. Here, we summarize our non-human primate and neuroimaging research of relevance to our surgical targeting of the PPN. We also describe our clinical experience of PPN DBS with greatest motor improvements achieved by stimulation at low frequencies.